# Application of Abelian distribution summation method (I.)

Source: Internet
Author: User

1. (and Difference transformation formula) set $m<n$.
$$\sum_{k=m}^{n} (A_{k}-a_{k-1}) B_{k}=a_{n}b_{n}-a_{m-1}b_{m}+\sum_{k=m}^{n-1}a_{k} (b_{k}-b_{k+1})$$
Proof: Direct calculation can be.
\begin{align*}
\sum_{k=m}^{n} (A_{k}-a_{k-1}) b_{k}&=\sum_{k=m}^{n}a_{k}b_{k}-\sum_{k=m}^{n}a_{k-1}b_{k}\\
&=\sum_{k=m}^{n}a_{k}b_{k}-\sum_{m-1}^{n-1}a_{k}b_{k+1}\\
&= (A_{n}b_{n}-a_{m-1}b_{m}) +\sum_{k=m}^{n-1}a_{k} (B_{k}-b_{k+1})
\end{align*}
2. (Division summation method) set $s_{k}=a_{1}+a_{2}+\cdots+a_{k}, (K=1,2,\cdots,n)$. Then
$$\sum_{k=1}^{n}a_{k}b_{k}=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k} (b_{k}-b_{k+1})$$
Proof: Supplementary definition $s_{0}=0$, using the conclusion of the first question can be. Make this proposition and the first question equivalent. \\
You may wish to set up a $m<n$, known
$$\sum_{k=1}^{n}a_{k}b_{k}=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k} (b_{k}-b_{k+1})$$
$$\sum_{k=1}^{m-1}a_{k}b_{k}=s_{m-1}b_{m-1}+\sum_{k=1}^{m-2}s_{k} (b_{k}-b_{k+1})$$
Two-type subtraction
$$\sum_{k=m}^{n}a_{k}b_{k}=s_{n}b_{n}-s_{m-1}b_{m-1}+\sum_{k=m-1}^{n-1}s_{k} (b_{k}-b_{k+1})$$\\
3. Set $s_{n}=a_{1}+a_{2}+\cdots+a_{n}\to s (n\to \infty)$, then
$$\sum_{k=1}^{n}a_{k}b_{k}=sb_{1}+ (S_{n}-s) b_{n}-\sum_{k=1}^{n-1} (S_{k}-s) (B_{k+1}-b_{k})$$
Proof: By the distribution of the sum of knowledge
$$\sum_{k=1}^{n}a_{k}b_{k}=s_{n}b_{n}-\sum_{k=1}^{n-1}s_{k} (B_{k+1}-b_{k})$$
and
s (b_{n}-b_{1}) =s\sum_{k=1}^{n-1} (B_{k+1}-b_{k}) $$The two-type subtraction is the conclusion. \\ 4. (Abell lemma) if for all n=1,2,3,\cdots  b _{1}\geq b_{2}\geq \cdots \geq b_{n}\geq 0$$
m \leq A_{1}+a_{2}+\cdot+a_{n}\leq m$$Then there are  b _{1}m\geq A_{1}b_{1}+a_{2}b_{2}+\cdots+a_{n}b_{n}\leq b_{1}m$$
Proof: Set $s_{k}=a_{1}+a_{2}+\cdots+a_{k}, (K=1,2,\cdots,n)$. Because $b_{k}\geq 0,b_{k}-b_{k+1}\geq 0$
$$\sum_{k=1}^{n}a_{k}b_{k}=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k} (B_{k}-b_{k+1}) \leq b_{n}m+m\sum_{k=1}^{n-1} (b_{k}-b _{K+1}) =b_{1}m$$
The left inequality proves similar
$$\sum_{k=1}^{n}a_{k}b_{k}=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k} (B_{k}-b_{k+1}) \geq b_{n}m+m\sum_{k=1}^{n-1} (b_{k}-b _{K+1}) =b_{1}m$$\\
5. Set $a_{1},a_{2},\cdots,a_{n},b_{1},b_{2},\cdots,b_{n}$ to any real or complex number, and set
A =\max \{|a_{1}|,|a_{1}+a_{2}|,\cdots,|a_{1}+a_{2}+\cdots+a_{n}|\}$$The$$\left|\sum_{k=1}^{n}a_{k}b_{k}\right|\leq a \left\{\sum_{k=1}^{n-1}|b_{k+1}-b_{k}|+|b_{n}|\right\}$$Proof: Use absolute value inequality to indent.$$\left|\sum_{k=1}^{n}a_{k}b_{k}\right|\leq |s_{n}|\times|b_{n}|+\sum_{k=1}^{n-1}|s_{k}|\times |b_{k}-b_{k+1}|\ Leq A \left\{\sum_{k=1}^{n-1}|b_{k+1}-b_{k}|+|b_{n}|\right\}$$6. (Kronecker) Set \varphi (n) >0,\varphi (n) \uparrow \infty (n \to \infty) . Also set \sum_{n=1}^{\infty}a_{n} convergence. The$$\sum_{k=1}^{n}a_{k}\varphi (k) =o (\varphi (n)), (n\to \infty) $$Proof: Set s_{n}\to s (n\to \infty)  then for any \varepsilon>0 existence m>0,n>m$$|s_{n}-s|<\varepsilonBy the Division summation method (repeat the third question of the second question) step \begin{align*} \sum_{k=1}^{n}a_{k}b_{k}&=s\varphi (1) + (s_{n}-s) \varphi (n)-\sum_{k=1}^{n-1} (S_{k}-s) (\varphi (k+1)-\varphi (k ))\\ &=o (1) +o (\varphi (n))-\sum_{k=1}^{m} (S_{k}-s) (\varphi (k+1)-\varphi (k))-\sum_{k=m+1}^{n-1} (S_{k}-s) (\varphi ( k+1)-\varphi (k)) \ \ &\leq O (1) +o (\varphi (n)) +\varepsilon (\varphi (n)-\varphi (m+1)) \end{align*} Since \varphi (n) \to \infty, know \sum_{k=1}^{n}a_{k}\varphi (k) =o (\varphi (n)), (n\to \infty) \\ 7. Set \varphi (n) \downarrow 0 (n \to \infty) , and \sum_{n=1}^{\infty}a_{n}\varphi (n)  for convergence, then\lim_{n\to\infty} (A_{1}+a_{2}+\cdots+a_{n}) \varphi (n) =0$$Proof: Consider a_{n}\varphi (n)  as the a_{n} in Proposition 6, and \varphi^{-1} (n)  as the \varphi (n)  in Proposition 6, the proposition is proven. \\ \textbf{another certificate}: Direct use of the Abbe lemma proved. Any given \varepsilon>0, known by the Cauchy convergence Criterion, exists n, n >n$$-\frac{\varepsilon}{2}<a_{n}\varphi (n) +a_{n+1}\varphi{n+1}+\cdots+a_{n}\varphi (n) <\frac{\varepsilon}{2 }$$and a monotonically decreasing nonnegative column.$$\varphi^{-1} (N) \geq \varphi^{-1} (n-1) \geq \cdots\geq\varphi^{-1} (N) >0$$Redefine the sequence, using the Abell lemma Proposition 4, which is$$|a_{n}+a_{n+1}+\cdot+a_{n}|<\varphi^{-1} (N) \frac{\varepsilon}{2}$$That$$| (A_{n}+a_{n+1}+\cdot+a_{n}) \varphi (n) |<\varphi^{-1} (N) \frac{\varepsilon}{2}$$Because \varphi (n) \to 0,n\to \infty$$\limsup| (A_{1}+\cdots+a_{n-1}+a_{n}+\cdots+a_{n}) \varphi (N) |\leq 0+\frac{\varepsilon}{2}$$The proposition is to be proven. \ \ 8. (Dirichlet) Set \sigma>0, the following Dirichlet series  a _{1}\cdot 1^{-\sigma}+a_{2}\cdot 2^{-\sigma}+a_{2}\cdot 3^{-\sigma}+\cdots+a_{n}\cdot n^{-\sigma}+\cdots$$
When convergent, there must be
$$\lim_{n\to\infty} (A_{1}+a_{2}+\cdots+a_{n}) n^{-\sigma}=0$$
Proof: This proposition is a special case of Proposition 7. \\
9. Set $\{z_{n}\}_{1}^{\infty}$ to any one complex column and
$$\sum_{n=1}^{\infty}|z_{n+1}^{-1}-z_{n}^{-1}|=\infty$$
and set the series $\sum_{n=1}^{\infty}a_{n}z_{n}$ for convergence, then there must be
$$\lim_{n\to\infty}\left (\sum_{n=1}^{n}a_{n}\right) \left (\sum_{n=1}^{n}|z_{n+1}^{-1}-z_{n}^{-1}|\right) ^{-1}=0$$
Proof: This type of topic is the $|\sum a_{n}|$ estimate, set $s_{n}=\sum_{k=1}^{n}a_{k}z_{k},s_{n}\to s (n\to \infty)$, there is an estimate
\begin{align*}
\left|\sum_{n=1}^{n}a_{n}\right|&=\left|\sum_{n=1}^{n}\left (a_{n}z_{n}\right) z_{n}^{-1}\right|\\
&=\left|\sum_{n=1}^{n} (S_{n}-s_{n-1}) z_{n}^{-1}\right|\\
&=\left|\sum_{n=1}^{n}s_{n}z_{n}^{-1}-\sum_{n=1}^{n}s_{n-1}z_{n}^{-1}\right|\\
&=\left|s_{n}z_{n}^{-1}+\sum_{n=1}^{n-1}s_{n} (Z_{n}^{-1}-z_{n+1}^{-1}) \right|\\
&=\left|s_{n}z_{n+1}^{-1}+\sum_{n=1}^{n}s_{n} (Z_{n}^{-1}-z_{n+1}^{-1}) \right|\\
&=\left| (s_{n}-s) Z_{n+1}^{-1}+s z_{1}^{-1}+\sum_{n=1}^{n} (S_{n}-s) (z_{n}^{-1}-z_{n+1}^{-1}) \right|
\end{align*}
Known by $\lim_{n\to \infty}s_{n}-s=0$, existence $m$, when $n>m$, $|s_{n}-s|<\varepsilon$
Therefore, the right side of the above equation can be shrunk
\begin{align*}
R&\leq \left| (s_{n}-s) Z_{n+1}^{-1}) \right|+\left|sz_{1}^{-1}\right|+\left|\sum_{n=1}^{m} (S_{n}-s) (z_{n}^{-1}-z_{n+1}^{-1}) \ Right|+\left|\sum_{n=m}^{n} (S_{n}-s) (z_{n}^{-1}-z_{n+1}^{-1}) \right|\\
&\leq\varepsilon |z_{n+1}^{-1}|+\left|sz_{1}^{-1}\right|+\varepsilon \left|z_{n}^{-1}-z_{n+1}^{-1}\right|+\ Left|\sum_{n=1}^{m} (S_{n}-s) (z_{n}^{-1}-z_{n+1}^{-1}) \right|\\
&=\varepsilon |z_{n+1}^{-1}|+\varepsilon\sum_{m}^{n}\left|z_{n}^{-1}-z_{n+1}^{-1}\right|+m
\end{align*}
So
\begin{align*}
\frac{\left|\sum_{n=1}^{n}a_{n}\right|} {\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} &\leq\varepsilon \cdot \frac{|z_{n+1}^{-1}|} {\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} +\frac{m}{\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} +\varepsilon \cdot \frac{\sum_{m}^{n}\left|z_{n}^{-1}-z_{n+1}^{-1}\right|} {\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} \\
&\leq \varepsilon+\frac{m}{\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} +\varepsilon
\end{align*}
Thus
$$\limsup \frac{\left|\sum_{n=1}^{n}a_{n}\right|} {\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} \leq 2\varepsilon$$
Since $\varepsilon$ is an arbitrary number
$$\limsup \frac{\left|\sum_{n=1}^{n}a_{n}\right|} {\sum_{n=1}^{n}\left|z_{n+1}^{-1}-z_{n}^{-1}\right|} =0$$
Proof Method: Abelian Division summation method + piecewise estimate + upper limit. \\
10. When $k=1,2,3,\cdots$ is established, there is
b _{k}\geq b_{k+1},\frac{1}{2} (b_{k}+b_{k+1}) \geq b_{k+1}$$And  m \leq S_{1}+s_{2}+\cdots+s_{k}\leq m$$
Where $s_{k}=a_{1}+a_{2}+\cdots+a_{k}$. The following inequalities are established
m (b_{1}-b_{2}) +s_{n}b_{n}<\sum_{k=1}^{n}a_{k}b_{k}<m (b_{1}-b_{2}) +s_{n}b_{n}$$Proof: Set  M _{n}=\sum_{k=1}^{n}s_{k},\, \tilde{b}_{k}=b_{k}-b_{k+1}$$
by $b_{k}+b_{k+2}\geq 2b_{k+1}$ $\tilde{b}_{k}\geq \tilde{b}_{k+1}$. Summation Formula by distribution
\begin{align*}
\sum_{k=1}^{n}a_{k}b_{k}&=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k} (b_{k}-b_{k+1}) \ \
&=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k}\tilde{b}_{k}\\
&=s_{n}b_{n}+m_{n-1}\tilde{b}_{n-1}+\sum_{k=1}^{n-2}m_{k} (\tilde{b}_{k}-\tilde{b}_{k+1}) \ \
&\leq s_{n}b_{n}+m\tilde{b}_{n-1}+m\sum_{k=1}^{n-2} (\tilde{b}_{k}-\tilde{b}_{k+1}) \ \
&=s_{n}b_{n}+ (b_{1}-b_{2}) M
\end{align*}
The left inequality proves similar. \\
11. Set $n$ as a fixed large integer, $a _{1},a_{2},\cdots,a_{n},b_{1},b_{2},\cdots,b_{n}$ for any two sets of constants. This definition $b_{k}=0 (k>n)$ and
$$\delta^{m}b_{k}=\delta^{m-1}b_{k+1}-\delta^{m-1}b_{k},\, \delta b_{k}=b_{k+1}-b_{k}$$
s _{k}^{(m)}=\sum_{\nu=1}^{k}s_{\nu}^{(m-1)},s_{k}^{(1)}=a_{1}+a_{2}+\cdots+a_{k}$$The following identities are established:$$\sum_{k=1}^{n}a_{k}b_{k}= ( -1) ^{m}\sum_{k=1}^{n}s_{k}^{(m)}\delta^{m}b_{k}Proof: The repeated use of the distribution summation formula can be \begin{align*} \sum_{k=1}^{n}a_{k}b_{k}&=s_{n}b_{n}+\sum_{k=1}^{n-1}s_{k}\left (-\delta b_{k}\right) \ \ &=s_{n}b_{n}+s_{n-1}^{(2)}\left (-\delta b_{n-1}\right) +\sum_{k=1}^{n-2}s_{k}^{2}\left (\Delta^{2} b_{k}\right )\\ &=s_{n}^{(1)}b_{n}+s_{n-1}^{(2)}\left (-\delta b_{n-1}\right) +s_{n-2}^{(3)}\left (\delta^{2} b_{N-2}\right) +\ cdots+ ( -1) ^{n-1}s_{1}^{(N)}\delta^{n-1}b_{1}\\ &=\sum_{k=1}^{n} ( -1) ^{k-1}s_{n-k+1}^{(k)}\delta^{k-1}b_{n-k+1} \end{align*} 12. Set a_{k}>0,b_{k}>0, and \{v_{k}\} as a monotone descending positive sequence. Also set  H =\max\left (\frac{b_{0}}{a_{0}},\frac{b_{1}}{a_{1}},\cdots,\frac{b_{n}}{a_{n}}\right), \,\,h=\min\left (\frac{ B_{0}}{a_{0}},\frac{b_{1}}{a_{1}},\cdots,\frac{b_{n}}{a_{n}}\right)
H _{m}=\max\left (\frac{b_{m}}{a_{m}},\frac{b_{m+1}}{a_{m+1}},\cdots,\frac{b_{n}}{a_{n}}\right), \,\,h_{m}=\min \left (\frac{b_{m}}{a_{m}},\frac{b_{m+1}}{a_{m+1}},\cdots,\frac{b_{n}}{a_{n}}\right) $$Here a_{k}=a_{1}+a_{2}+\cdots+a_{k},\, b_{k}=b_{1}+b_{2}+\cdots+b_{k}. the following inequalities are established:  h _{m}+ (h-h_{m}) \frac{\sum_{k=0}^{m}a_{k}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}\leq \frac{\sum_{k=0}^{n}b_{k}v_{k}}{ \sum_{k=0}^{n}a_{k}v_{k}}\leq h_{m}+ (h-h_{m}) \frac{\sum_{k=0}^{m}a_{k}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}$$
Proof: Partial summation method + piecewise estimation, only the left inequality of right inequality proves similar.
\begin{align*}
\frac{\sum_{k=0}^{n}b_{k}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}-h_{m}&=\frac{\sum_{k=0}^{m-1}b_{k} (V_{k}-v_{k+1} ) +\sum_{k=m}^{n}b_{k} (V_{k}-v_{k+1}) +b_{n}v_{n}}{\sum_{k=0}^{n}a_{k} (v_{k}-v_{k+1}) +a_{n}v_{n}}-h_{m}\\
&\leq \frac{h\sum_{k=0}^{m-1}a_{k} (V_{k}-v_{k+1}) +h_{m}\sum_{k=m}^{n}a_{k} (v_{k}-v_{k+1}) +H_{m}A_{n}v_{n}}{ \sum_{k=0}^{n}a_{k} (v_{k}-v_{k+1}) +a_{n}v_{n}}-h_{m}\\
&=\frac{(H-h_{m}) \sum_{k=0}^{m-1}a_{k} (V_{k}-v_{k+1})}{\sum_{k=0}^{n}a_{k} (v_{k}-v_{k+1}) +A_{n}v_{n}}\\
&\leq (H-h_{m}) \frac{\sum_{k=0}^{m}a_{k}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}
\end{align*}
13. Retain all assumptions of Proposition 12, but change the $\{v_{n}\}$ to a monotonically ascending sequence. Then there are
H _{m}-\frac{(h_{m}-h_{m}) a_{n}v_{n}+ (H-h_{m}) A_{m}v_{m}}{\sum_{k=0}^{n}a_{k}v_{k}}\leq \frac{\sum_{k=0}^{n}b_ {K}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}\leq h_{m}+\frac{(h_{m}-h_{m}) a_{n}v_{n}+ (h_{m}-h) A_{m}v_{m}}{\sum_{k=0}^{n} a_{k}v_{k}}
Proof: Partial summation method + piecewise estimation, only the left inequality of right inequality proves similar.
\begin{align*}
\frac{\sum_{k=0}^{n}b_{k}v_{k}}{\sum_{k=0}^{n}a_{k}v_{k}}-h_{m}&=\frac{\sum_{k=0}^{m-1}b_{k} (V_{k}-v_{k+1} ) +\sum_{k=m}^{n}b_{k} (V_{k}-v_{k+1}) +b_{n}v_{n}}{\sum_{k=0}^{n}a_{k} (v_{k}-v_{k+1}) +a_{n}v_{n}}-h_{m}\\
&=\frac{\sum_{k=0}^{m-1} (B_{k}-h_{m}a_{k}) (V_{k}-v_{k+1}) +\sum_{k=m}^{n} (B_{k}-h_{m}a_{k}) (v_{k}-v_{k+1}) + (B_{n}-h_{m}a_{n}) V_{n}}{\sum_{k=0}^{n}a_{k} (v_{k}-v_{k+1}) +a_{n}v_{n}}\\
&\leq\frac{(H_{m}-h_{m}) a_{n}v_{n}+ (H_{m}-h) A_{m}v_{m}}{\sum_{k=0}^{n}a_{k}v_{k}}
\end{align*}

Application of the summation method of abelian distributions (i)

Related Keywords:

### Contact Us

The content source of this page is from Internet, which doesn't represent Alibaba Cloud's opinion; products and services mentioned on that page don't have any relationship with Alibaba Cloud. If the content of the page makes you feel confusing, please write us an email, we will handle the problem within 5 days after receiving your email.

If you find any instances of plagiarism from the community, please send an email to: info-contact@alibabacloud.com and provide relevant evidence. A staff member will contact you within 5 working days.

## A Free Trial That Lets You Build Big!

Start building with 50+ products and up to 12 months usage for Elastic Compute Service

• #### Sales Support

1 on 1 presale consultation

• #### After-Sales Support

24/7 Technical Support 6 Free Tickets per Quarter Faster Response

• Alibaba Cloud offers highly flexible support services tailored to meet your exact needs.